The status rights of the child and the search for a new paradigm of parenthood in Czechia - Králíčková, Zdeňka (European Integration Studies, 2025)
The traditional concept of the status rights of a child, which is based on the concept of natural law that the mother of the child is the woman who gave birth to the child and the father is the man determined by the time-honoured presumption of paternity, has been disturbed in recent years. Many States are now faced with requests from their citizens to register a foreign-born child, particularly through surrogacy. These often involve not only married or unmarried couples, both heterosexual and homosexual, but also individuals. Assisted reproduction, and the “reproductive tourism” frequently associated with it, is a challenge, not only for the “conservative legislator” but also for the “old-world registrar” recording the birth of a child in the public registers, or for the “rigid judge” deciding on the recognition of a foreign public document when the registry office “sticks to” the old order. However, it encompasses not just the controversial issue of assisted reproduction, or surrogacy, but much more: a fresh perspective on family law, family life, parenthood, human rights – including the rights of the child, or the best interests of the child – in the context of public policy, or public order.